Research on the health state of the Sicilian population living in areas at environmental or natural risk: the experience of the Regional Department of Epidemiology (Italian Journal of Public Health, 2008)
Background: In Sicily, people live near areas characterized by the presence of environmental polluting substances derived from urbanization and industrialization. In the areas of Augusta-Priolo (SR),Gela (CL) and Milazzo (ME), the increase of number of pathologies could be linked with environmental pollution. The aim of this paper is to present an overview of the available data and studies to underline the importance of these sources to conduct epidemiological survey in Sicily, besides to the analysis of mortality and morbidity.Methods: An evaluation of the health status of the residential population was done comparing the mortality and morbidity of the local population with the mortality and morbidity of a reference population. Data was obtained from the Italian national office of statistics and Hospital Discharge Records. Standardized Mortality Ratios and Standardized Hospitalization Ratios were calculated.Results: In the area of Augusta-Priolo we observed, in for men, a significative increase in mortality and hospital admissions for colon-rectal, trachea, bronchus, lung and pleura cancers. In Biancavilla, we observed an increase in mortality for pleura cancer in men and women and an increase in morbidity in women only. In Gela, a significant increase in mortality in males and females was observed only for tumoral diseases. In Milazzo, we only found a significant increase in the incidence of larynx cancer and cardiovascular disease for men and in women of pulmonary disease for women.Conclusions: This first review allowed us to update previous analyses of mortality data conducted in the same areas. The results, even taking into account the differences between the areas,, highlights changes in health status related to some diagnostic groups. These could be linked with pollution. Now that the available health data has been revised and updated new studies must be conducted.
Keywords: Health state; environmental; pollution; Sicily